Janice VanCleave's geography for every kid : easy activities that make learning geography fun. - VanCleave, Janice Pratt (New York : Wiley, 1993)
Introduces basic concepts of geography through simple problems and activities such as constructing a clay map, making a compass rose, and plotting the track of a hurricane.
Includes index.
Appraisal-Science Books for Young People.
Horn Book.
6.6.
6.6
5-8
Keywords: Geography -- Juvenile literature; Geography; Geography